THE RELATIONSHIP BETWEEN SELF-CONFIDENCE AND EMOTIONAL INTELLIGENCE WITH STUDENTS MATHEMATICS LEARNING OUTCOME - Nika Riztia Permata; Edi Prajitno (Universitas Ahmad Dahlan, 2018)
This study aims to determine whether there is a positive and significant relationship between self-confidence and emotional intelligence with the math results in class VIII even semester at State Junior High School 2 Purwodadi (SMP Negeri 2 Purwadadi) Ciamis regency. The academic year of 2017/2018. This research sample is VIII class student at even semester in SMP Negeri 2 Purwadadi Regency of Ciamis academic year 2017/2018, which consists of class VIIIA, VIIIB, and VIIIC that consist of 71 students. The sample was taken from class VIIIA with a random sampling technique to the class. Data collection techniques used questionnaire method to obtain self-confidence data and emotional intelligence and test methods to obtain data of mathematics learning result Data analysis using product moment analysis and multiple linear regression analysis. The results showed a positive and significant relationship between self-confidence with the results of learning mathematics class VIII Semester Even SMP Negeri 2 Purwadadi Ciamis Regency Year 2017/2018. This is shown by the test- t is t_count > t_table or 2,9720 > 2.0595. The simple correlation coefficient (r) between self-confidence and mathematics learning result of 0,5110 with linear regression equation Y Ì‚ = 35,0491 + 0,3939 X_1. There is a positive and significant relationship between emotional intelligence with mathematics learning outcomes of students of class VIII Semester Even SMP Negeri 2 Purwadadi Ciamis Regency Year 2017/2018. The test indicates this- t is tcount > ttable or 3.0221 > 2.0595. Simple correlation coefficient (r) between emotional intelligence with mathematics learning result of 0,5173 with linear regression equation Y Ì‚ = 28,1534 + 0,4740 X_2. there is a positive and significant relationship between self-confidence and emotional intelligence with the result of learning mathematics with Fcount > Ftable is 7,4311> 3,4028 with R = 0,6184 and R2 = 0,3824 with Y Ì‚ = 15,8994 + 0, 2828X_1 + 0.3454X_2 with RC X_1= 49,0058% and RC X_2 = 50,9942% EC X_1 = 18,7415% and EC X_2 = 19,5019%.